Impacts of meso-scale watershed development in Andhra Pradesh (India) and their implications for designing and implementing improved WSD policies and programs - Croke, B.; Herron, N.; Pavelic, Paul; Ahmed, S.; Reddy, V.R.; Ranjan, R.; Syme, G.J.; Samad, M.; Rao KV (IWA Publishing, 2012)
Watershed Development (WSD) programs in rainfed dryland agriculture in India have been introduced in an effort to promote more sustainable management of the surface and groundwater resources, and to improve the livelihoods of farmers. This paper outlines the planned research for a project exploring the impacts of WSD at the meso-scale (~100 km2). The aim of the project is to develop and apply integrated models to assess cost effectiveness and water-related equity outcomes of stakeholder defined WSD scenarios; and to integrate and apply, in collaboration with project partners, the knowledge arising from the project at local, state and national policy levels.